Occupational, Commuting, and Leisure-Time Physical Activity in Relation to Cardiovascular Mortality Among Finnish Subjects With Hypertension - Hu, Gang; Jousilahti, Pekka; Antikainen, Riitta; Tuomilehto, Jaakko (American journal of hypertension, 2007)
The association between different types of physical activity and cardiovascular risk among hypertensive subjects is not fully understood. The purpose of this study was to determine the association of occupational, commuting, and leisure-time physical activity on cardiovascular mortality among hypertensive patients. Study cohorts included 26,643 hypertensive Finnish men and women who were aged 25 to 64 years and free of coronary heart disease, stroke, and Type 1 diabetes. During a mean follow-up of 19.9 years (range, 6.6 to 31.7 years), 3743 subjects died because of cardiovascular disease. The multivariate-adjusted (age, study year, education, alcohol consumption, smoking, body mass index, systolic blood pressure, total cholesterol, use of antihypertensive drugs, and diabetes at baseline or during follow-up, and the other two kinds of physical activity) hazard ratios of cardiovascular mortality associated with low, moderate, and high occupational physical activity were 1.00, 0.84, and 0.86 ( P for trend = .006), respectively, for hypertensive men, and 1.00, 0.85, and 0.84 ( P for trend = .014), respectively, for hypertensive women. The multivariate-adjusted hazard ratios of cardiovascular mortality associated with low, moderate, and high leisure-time physical activity were 1.00, 0.84, and 0.73 ( P for trend < .001), respectively, for hypertensive men, and 1.00, 0.78, and 0.76 ( P for trend < .001), respectively, for hypertensive women. Active commuting to and from work was significantly associated with reduced cardiovascular mortality in hypertensive women. Moderate or high levels of occupational or leisure-time physical activity reduce cardiovascular mortality among both men and women with hypertension. Walking or cycling to and from work daily reduces cardiovascular mortality among hypertensive women.